F(-3)=2x2-5x+3

Simple and best practice solution for F(-3)=2x2-5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(-3)=2x2-5x+3 equation:



(-3)=2F^2-5F+3
We move all terms to the left:
(-3)-(2F^2-5F+3)=0
We add all the numbers together, and all the variables
-(2F^2-5F+3)-3=0
We get rid of parentheses
-2F^2+5F-3-3=0
We add all the numbers together, and all the variables
-2F^2+5F-6=0
a = -2; b = 5; c = -6;
Δ = b2-4ac
Δ = 52-4·(-2)·(-6)
Δ = -23
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 2u+38=7u-12 | | 1/2(2x+9)=25/2 | | u/12=3/8 | | x-5/3=-1 | | 7(-3/7x+1)=-20 | | v+4/5=-1/2 | | (x+2)(x-3)=x+9 | | 7x+40=40 | | 64*x-5*x^2-195=0 | | -4=w-3/5 | | x-50=29 | | 3(2n+1)+5=68 | | -29=-x/9 | | 17^(-x)=4 | | 3(2n=1)+5=68 | | -0.4x^2-3x+20=5 | | n/8+-3=-11 | | 17^-x=4 | | 10x+6+114=180 | | 6x+6=7+2x | | X+.1x=30 | | X^2+(9-x)^2=101 | | 2(x-4)+4(2x=1) | | (2x+5)•(12)=(2x+2)•(14) | | 2x=16;x= | | 9x+6=4x-36 | | 8+5x=x-16 | | 2x=16;x | | 4(x+7)=7-5x | | 0.23x^2+4x+9=15 | | 8+6x=2/3x+56/3 | | 13x-5=81 |

Equations solver categories